Athlete`s heart or heart disease in the athlete? Evaluation by cardiopulmonary exercise testing - Segreti, A.; Picarelli, F.; Di Gioia, G.; Coletti, F.; Crispino, S. P.; Fanale, V.; Fossati, C.; Antonelli Incalzi, R.; Pigozzi, F.; Grigioni, F. (The Journal of Sports Medicine and Physical Fitness, 2023)
Routine or vigorous training, particularly in competitive and elite athletes practicing dynamic sports, leads to a constellation of structural and functional cardiovascular adaptations, facilitating an increased capacity to deliver oxygen to the working muscles during sustained physical exertion. Cardiopulmonary exercise testing is the most accurate and objective method to assess performance in athletes. Although still underutilized, it provides a window into the unique cardiovascular response to exercise in athletes, integrating parameters obtained by the traditional exercise test with breath-by-breath analysis of oxygen consumption, carbon dioxide production, ventilation, and other derived parameters. This review aimed to describe the several applications of cardiopulmonary exercise testing in athletes with a principal focus on the ability to identify cardiovascular adaptations and differentiate an athlete`s heart from early cardiomyopathy. In this context, cardiopulmonary exercise testing provides many applications involving exercise physiology in athletes, allowing a precise evaluation of cardiovascular efficiency, the entity of the adaptations, the response to a training program, and identifying early modifications that could reveal early cardiomyopathy. Therefore, thanks to its several applications, this pivotal test allows us to obtain essential information about the athlete`s physiology and differentiate between the expected response of a trained athlete from early cardiomyopathy.